Low-body-perfusion via an arterial sheath reduces inflammation after aortic arch reconstruction surgery. (March 2021) - Baehner, Torsten; Breuer, Johannes; Heinze, Ingo; Duerr, Georg Daniel; Dewald, Oliver; Velten, Markus
Pediatric cardiac surgeries involving aortic arch reconstruction are complex and require long cardiopulmonary bypass (CPB) times with deep hypothermic circulatory arrest (DHCA). Selective perfusion techniques have been developed to prevent the deleterious consequences of DHCA associated hypoperfusion. The effectivity of low body perfusion through cannulation of the femoral artery with an arterial sheath remains to be elucidated. We compared perfusion and inflammation in patients receiving selective antegrade cerebral perfusion (ACP) only to low body perfusion (LBP) in addition to ACP during DHCA for aortic arch reconstruction surgery. There was no difference in patient characteristics, cardiac pathologies, or performed procedures between ACP and LBP groups. Lactate levels increased after cardiac arrest in both groups. However, lactate levels were lower after 1 h reperfusion, at the end of extracorporeal circulation (ECC), and after surgery in LBP group compared to ACP only. Furthermore, creatinine was increased in ACP group on postoperative day 1 compared to LBP group but no acute kidney injury was observed in any group. IL-6 concentration increased in ACP group, while remained unchanged in LBP group compared to pre surgical values and were significantly lower compared to ACP group on postoperative days 1 and 2. LBP via an arterial sheath during cardiac arrest for aortic arch reconstruction surgery in addition to ACP, improves post ECC tissue perfusion as indicated by lower lactate levels and reduces creatinine levels suggesting milder kidney injury. LBP seems to prevent postoperative inflammation through a reduction in procedural duration or enhanced perfusion and thereby improves the outcome after aortic arch reconstruction surgery.